2021
DOI: 10.1109/access.2021.3123818
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Apparently Poor Conductivity of Galvanized Steel Plates

Abstract: This paper investigates the physical reasons for the apparently poor conductivity of galvanized steel plates (GSP), which has not yet received a proper explanation. Apparent conductivities as low as 0.1 MS/m were reported in the past, which are incongruously low compared to the DC conductivity of steels (4 to 8 MS/m), or zinc (16.7 MS/m), the most common coating agent used against corrosion in steel products. A comprehensive review of results from metallurgy and materials science is presented, providing insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…2 and 3 will underestimate the input power used for EMC tests, and therefore lead to the overestimate the performance of the equipment under test. Referring to [10] again, it is found that the conductivity of galvanized steel may be as low as 10 kS/m. However, it is not possible to ensure a good fit for all the frequency range if the conductivity is set to 10 kS/m.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…2 and 3 will underestimate the input power used for EMC tests, and therefore lead to the overestimate the performance of the equipment under test. Referring to [10] again, it is found that the conductivity of galvanized steel may be as low as 10 kS/m. However, it is not possible to ensure a good fit for all the frequency range if the conductivity is set to 10 kS/m.…”
Section: Resultsmentioning
confidence: 97%
“…Otherwise, the numerical Q factor will overestimate the chamber performance, resulting in a low field with respect to the limit level for EMC tests. As discussed in [10,12], the galvanized steel contains a complex ironzinc structure, which cannot be simple regarded as iron or zinc. Moreover, considering the skin depth, it is barely impossible to establish an accurate mathematical model for describing the reflections of incident waves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation